A review of the genus Engystenopus (Crustacea: Decapoda: Stenopodidea) Juxtastenopus, gen. nov. , a new combination for E. spinulatus Holthuis, 1946, and transfer of E. palmipes Alcock & Anderson, 1894 to the family Spongicolidae Schram, 1986 - Goy, Joseph W. (Zootaxa, 2010)
A review of the genus Engystenopus is presented. A new genus, Juxtastenopus, is created for the rare deepwater stenopodid shrimp, Engystenopus spinulatus based on a series of specimens from the Red Sea, Gulf of Aden and the Philippines. The genus Engystenopus is now restricted to E. palmipes, its range is extended to Australian, Indonesian, and Madagascan waters, a new diagnosis of the genus is presented, and the genus is transferred to the family Spongicolidae.